Non-precious cobalt phthalocyanine-embedded iron ore electrocatalysts for hydrogen evolution reactions. Issue 5 (15th February 2021) - CP, Keshavananda Prabhu; Aralekallu, Shambhulinga; Sajjan, Veeresh A.; Palanna, Manjunatha; Kumar, Sharath; Sannegowda, Lokesh Koodlur
Abstract : Efficient water splitting reactions lead to sustainable hydrogen production, which is the fuel for fuel cell devices for clean energy production. Abstract : Efficient water splitting reactions lead to sustainable hydrogen production, which is the fuel for fuel cell devices for clean energy production. Better efficiency of hydrogen evolution reactions is achieved by the development of highly active non-precious electrocatalysts. In this work, a cobalt phthalocyanine-embedded iron ore particle hybrid composite was prepared for the electrochemical hydrogen evolution reaction (HER). First, cobalt tetrabenzimidazole phthalocyanine (CoTBImPc) was synthesized and characterized by different analytical and spectroscopic techniques. Then, iron ore particles obtained by ball milling were mixed with CoTBImPc to obtain a hybrid composite. Electrical conductivity studies revealed the semiconducting nature of the synthesized phthalocyanine molecule, whereas the composite of magnetite and phthalocyanine showed better conductive behaviour when its composition is in the ratio of 1 : 7.5. The organic hybrid composite was immobilized on a glassy carbon electrode (GCE/Fe3 O4 –CoTBImPc) and used for the hydrogen evolution reaction (HER). A remarkable HER activity was displayed by the composite hybrid material with a significant decrease in the overpotential. GCE/Fe3 O4 –CoTBImPc exhibited an overpotential of 49 mV at a current density of 10 mA cm −2, whereas the benchmark GCE/(Pt/C) showed an overpotential of 7.02 mV for HER at the same current density. The HER activity of the composite electrode is highly comparable to that of precious metal and metal oxide electrocatalysts used for HERs. The decrease in the overpotential for HER at the composite electrode is ascribed to the surface enhancement of the composite and improvement in the conductivity of CoTBImPc due to embedded Fe3 O4 particles. The Tafel slope of the composite electrode demonstrated a lower value than that of pristine phthalocyanines and Fe3 O4 particles, which is comparable to that of Pt/C. As the overpotential for the HER at the GCE/Fe3 O4 –CoTBImPc electrode reaches a value closer to that of the precious Pt/C electrode, the composite electrode can be used instead of the Pt/C electrode for HER applications.